Inhibition of the insulin-like growth factor system is a potential therapy for rheumatoid arthritis. (June 2015) - Suzuki, Satoshi; Morimoto, Shinji; Fujishiro, Maki; Kawasaki, Mikiko; Hayakawa, Kunihiro; Miyashita, Tomoko; Ikeda, Keigo; Miyazawa, Keiji; Yanagida, Mitsuaki; Takamori, Kenji; Ogawa, Hideoki; Sekigawa, Iwao; et al.
Abstract Objective: We have shown that connective tissue growth factor (CTGF) plays an important role in the pathogenesis of rheumatoid arthritis (RA). Insulin-like growth factor binding proteins (IGFBPs) are modules of CTGF. IGFBPs bind IGF-I and IGF-II. IGF-I plays a role in the regulation of immunity, bone metabolism and inflammation. Therefore, we investigated how the IGF system is associated with RA disease progression. Methods: Serum samples were collected from RA patients. IGF-I and IGFBP-3 production were evaluated by enzyme-linked immunosorbent assay, real-time RT-PCR and indirect immunofluorescence microscopy. Osteoclastogenesis was evaluated using tartrate-resistant acid phosphatase staining, a bone resorption assay and osteoclast-specific enzyme production. Angiogenesis was examined by a tube formation assay using human umbilical vein endothelial cells. Results: The serum concentrations of IGFBP-3 in RA patients were greater than those in normal controls. IGF-I and IGFBP-3 were produced primarily by macrophages in the RA synovium. Furthermore, tumor necrosis factor-α could induce aberrant IGF-I and IGFBP-3 production in synovial fibroblasts. IGF-I and IGFBP-3 promoted the induction of osteoclast generation and morphological changes, in combination with M-colony stimulating factor and the receptor activator of NF-κB ligand. In addition, IGF-I and IGFBP-3 induced angiogenesis, as determined by the tube formation assay. These effects were neutralized by anti-IGF-IR monoclonal antibody (mAb). Conclusions: These results indicate that aberrant IGF-I and IGFBP-3 production plays a role in abnormal osteoclastic activation and angiogenesis in RA. This work supports future clinical exploration of anti-IGF-IR mAb in drug repositioning as a new treatment for RA.